2018
DOI: 10.1016/j.jacbts.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-Like Factors

Abstract: SummaryKrüppel-like factors (KLFs) are deoxyribonucleic acid–binding transcriptional factors that regulate various pathways that control metabolism and other cellular mechanisms. Various KLF isoforms have been associated with cellular, organ, or systemic metabolism. Altered expression or activation of KLFs has been linked to metabolic abnormalities, such as obesity and diabetes, as well as with heart failure. This review article summarizes the metabolic functions of KLFs, as well as the networks of different K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 243 publications
(372 reference statements)
1
37
0
Order By: Relevance
“…Vik-1 belongs to the Krüppel-like factors (KLFs) protein family, which regulate the metabolic pathways across various tissues. KLFs have been shown to interact with the components of atherosclerosis pathogenesis and have also been linked to metabolic abnormalities, including obesity and diabetes mellitus (Pollak et al, 2018). In line with our findings from KEGG enrichment analysis of co-expressed genes of ZNF655, Zhao et al (2016) constructed a genetic network based on gene-gene interactions and revealed that pathways involved in Alzheimer's disease, non-alcoholic fatty liver disease, and Huntington's disease were also associated with CAD risk.…”
Section: Discussionsupporting
confidence: 74%
“…Vik-1 belongs to the Krüppel-like factors (KLFs) protein family, which regulate the metabolic pathways across various tissues. KLFs have been shown to interact with the components of atherosclerosis pathogenesis and have also been linked to metabolic abnormalities, including obesity and diabetes mellitus (Pollak et al, 2018). In line with our findings from KEGG enrichment analysis of co-expressed genes of ZNF655, Zhao et al (2016) constructed a genetic network based on gene-gene interactions and revealed that pathways involved in Alzheimer's disease, non-alcoholic fatty liver disease, and Huntington's disease were also associated with CAD risk.…”
Section: Discussionsupporting
confidence: 74%
“…Several groups have described various approaches to identify all of the members of the SP/KLF family in human and mouse genomes, and the effects of these proteins in more detail [ 4 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. As shown in Figure 1 , the protein-binding domains within the protein structures of KLF Group 1 (KLF 3, 8, and 12) serve as transcriptional repressors through their interaction with the C-terminal binding protein (CtBP).…”
Section: Sp/klf Familymentioning
confidence: 99%
“…Insulin is a hormone produced in the pancreas that helps maintain the blood glucose homeostasis (47)(48)(49). Several members of the KLF family members, including KLF14, have confirmed roles in the regulation of insulin sensitivity [reviewed in (50)]. Yang et al used high-fat diet (HFD)-fed mice and leptin receptor-deficient (db/db) mice that have impaired insulin sensitivity and showed that there is significant down-regulation of Klf14 expression in skeletal muscle (51).…”
Section: The Role Of Klf14 In Cardiometabolic Disordersmentioning
confidence: 99%
“…Inhibition of SK1 resulted in accumulation of the lipid second messenger ceramides in liver cancer cells (54), while elevated muscle ceramides have been associated with muscle insulin resistance in obese humans (55). As such, some of the KLF14-mediated metabolic phenotypes may be attributed to regulation of lipid signaling via dysregulation of SK1 (50,53). Below we summarize the studies that elucidated the role of KLF14 in metabolically active organs.…”
Section: The Role Of Klf14 In Cardiometabolic Disordersmentioning
confidence: 99%